Las implicaciones del conflicto interno colombiano para las fronteras de Ecuador, Perú, Brasil y Venezuela, 2000-2005 - Moreano Urigüen, Hernán (2006)
The present article describes the situation of the bordering nations with Colombia: Ecuador, Peru, Brazil and Venezuela, in relation to the Plan Colombia –created on August, 2000 in order to eradicate the cultures of coca’s leaf and simultaneously to fight against groups lifted in weapon, FARC, ELN and AUC. Besides military topics, the article deals with the social situations and environment aspects in the most vulnerable zones –an area characterized for a great number of displaced and refugee, without any common agreement among nations for the prevention of conflicts.